Gun Violence: A Biopsychosocial Disease - Stephen W. Hargarten; E. Brooke Lerner; Marc Gorelick; Karen Brasel; Terri deRoon-Cassini; Sara Kohlbeck (Western Journal of Emergency Medicine, 2018)
Gun violence is a complex biopsychosocial disease and as such, requires a multidisciplinary approach to understanding and treatment. Framing gun violence as a disease places it firmly within medical and public health practice. By applying the disease model to gun violence, it is possible to explore the host, agent, and environment in which gun violence occurs, and to identify risk factors to target for prevention. This approach also provides an opportunity to address scientifically inaccurate assumptions about gun violence. In addition, there are many opportunities for medical communities to treat gun violence as a disease by considering and treating the biologic, behavioral, and social aspects of this disease. The medical community must answer recent calls to engage in gun violence prevention, and employing this model of gun violence as a biopsychosocial disease provides a framework for engagement.